A study of controlled ovarian stimulation with clomiphene citrate or letrozole in combination with gonadotropins and IUI in unexplained infertility - Madhusmita Hembram (Journal of Human Reproductive Sciences, 2017)
Aim: To compare the effect of clomiphene citrate (CC) + human menopausal gonadotropin (hMG) with letrozole + hMG on size, number of follicles, endometrial thickness, serum levels of oestradiol and progesterone and pregnancy rate. Settings and Design: Non-randomised interventional study. Patients and Methods: A total number of 60 patients in the age group of 20–35 years with unexplained infertility were divided into two groups, 30 in each. Group A received CC + hMG and group B received letrozole + hMG. In both the groups, ovulation was triggered by hCG followed by intrauterine insemination. Results: The number of follicles on day 8 were significantly higher in the CC + hMG group than that in the letrozole + hMG group. Serum oestradiol level was significantly higher in the CC + hMG group on day 10 and on the day of hCG administration. Pregnancy rate in the CC + hMG group was 23.3% and 13.3% in the letrozole + hMG group. Conclusion: The sequential protocol was cost-effective. CC + hMG could be a preferred ovarian stimulation protocol in couples with unexplained infertility with the added advantage of having no significant complications in properly monitored cycles.